Elementos facilitadores e dificultadores da adesão a ações de incentivo ao consumo de frutas e hortaliças - Larissa Morelli Ferraz Guimaraes (2016)
The regular consumption of fruit and vegetables (FV) is considered a protective factor for chronic non-communicable diseases. However, the consumption of this food group is short of recommendations advocated by the World Health Organization, constituting a worldwide problem. In this context, actions to encourage the FV consumption have been prioritized. But one of the challenges to the effectiveness of these actions is the low adherence usually checked. Thus, the objective of this study was to understand the elements that influence adherence to actions to encourage the consumption of FV among users of the Health Gym Programme (HGP) of Belo Horizonte, Minas Gerais. It is descriptive study with a qualitative approach. The survey was conducted in seven polos of the HGP of the city that received nutritional interventions to encourage the consumption of FV, based theoretically and methodologically in the dialogic and problematizing pedagogy of Paulo Freire and grounded in Transtheoretical Model. 45 semi-structured interviews were conducted with users of both sexes and three different age groups. The interviews were recorded and transcribed and submitted to thematic content analysis with the aid of NVivo10 software. Most of the respondents (60%) had high adherence to intervention. As facilitator of adherence to actions to encourage the consumption of FV were identified: HGP itself, the proximity of users and ease of access; the methodology used in the intervention, which emphasized the importance of the subject as the protagonist of interventions; the aspects inherent to the subject; the family support; and the link with the group, with the service and the team. Already the barriers were: housework and/ or external; the care of another; and personal commitments - these elements pass the aspect of timing of actions. The main strategy pointed to by the participants to overcome the difficult aspects was the alternative proposed by the research team to change the day /or time of participation in the intervention. The adherence of the intervention was high and the reflection on facilitators and barriers makes it possible to develop joint strategies to that in other actions, the adherence to be even higher. Noteworthy are two central points that favored adherence in this study and that can be used in other works: the methodology used in the intervention and the and flexibility for participation in actions.